Neo-Liberalism, Policy Incoherence and Discourse Coalitions Influencing Non-Communicable Disease Strategy; Comment on "How Neoliberalism Is Shaping the Supply of Unhealthy Commodities and What This Means for NCD Prevention" - Samantha Battams (Kerman University of Medical Sciences, 2020)
Lencucha and Thow have highlighted the way in which neo-liberalism is enshrined within institutional mechanisms and conditions the policy environment to shape public policy on non-communicable diseases (NCDs). They critique the strong (but important) focus of public health policy research on corporate interests and influence over NCD policy, and point toward neo-liberal policy paradigms shaping the relationship between the state, market and society as an area for critique and further exploration. They also importantly underline the way in which the neo-liberal policy paradigm shapes the supply of unhealthy goods and argue that health advocates have not engaged enough with supply side issues in critiques of policy debates on NCDs. This is an important consideration especially in the Asia-Pacific where trade and agricultural policies have markedly shaped production and what is being produced within countries. In this commentary, I reflect upon how neoliberalism shapes intersectoral action across trade, development and health within and across institutions. I also consider scope for international civil society to engage in advocacy on NCDs, especially where elusive 'discourse coalitions' influenced by neoliberalism may exist, rather than coordinated 'advocacy coalitions.'